Co-infection with hepatitis B and human immunodeficiency virus: epidemiology, pathogenesis, and treatment - Yaozu He; Weiyin Lin; Fei Gu; Xianglong Lan; Linghua Li; Haijuan Wang (​​​​​​​​Infectious Diseases & Immunity)
Abstract. Co-infection with hepatitis B virus (HBV) and human immunodeficiency virus (HIV) is common as the modes of disease transmission are similar. HIV affects the development of chronic HBV infection, leading to higher HBV DNA levels, cirrhosis, and end-stage liver duisease, and potentially leading to hepatocellular carcinoma. One of the leading causes of mortality and morbidity in HIV-infected individualsis liver disease, despite the administration of antiretroviral therapy for HIV and HBV. Thus, the screening and follow-up of co-infected patients are vital formonitoring of liver disease progression. This study reviews the natural history and pathogenesis of liver disease in the context of HBV/HIV co-infection, current treatments for HBV in patients with HIV, and treatment outcomes in coinfected individuals.